Development of a 3D Augmented Reality Quizizz Learning Media Prototype in Implementing the Independent Learning Management in Schools - Mesterjon Mesterjon; Suwarni Suwarni; Khairil Khairil; Roy Syahputra; David Alvindo (Program Studi DIII Rekam Medis dan Informasi Kesehatan, 2024)
This study aims to develop a learning media prototype based on the Quizizz application, combined with 3D Augmented Reality (AR) technology, to support the implementation of Merdeka Belajar management in schools. AR technology enables the integration of virtual objects into real-world environments in real time, creating an interactive and engaging learning experience for students. Validation tests conducted at SMK N 03 Kota Bengkulu revealed that students experienced enjoyable and interactive learning, especially in the hardware introduction subject for the Computer and Network Engineering (TKJ) program. This prototype also supports teachers and educational institutions in implementing the Merdeka Belajar curriculum and can be used by parents and students as a learning aid at home. Furthermore, test results indicate that this media can serve as a supportive tool for the Merdeka Belajar Kampus Merdeka (MBKM) program. This prototype holds significant commercial potential through subscription or licensing models for schools and educational institutions, along with AR content that can be tailored to specific curriculum needs. The key advantages of this innovation include interactivity, support for learning flexibility, integration of cutting-edge technology, and accessibility through common devices like smartphones and tablets. The development stages include research and development, prototype creation, testing, product launch, as well as ongoing maintenance and feature enhancement.